Wilms tumour - Spreafico, Filippo; Fernandez, Conrad V.; Brok, Jesper (Nat Rev Dis Primers, 2021)
Wilms tumour (WT) is a childhood embryonal tumour that is paradigmatic of the intersection between disrupted organogenesis and tumorigenesis. Many WT genes play a critical (non-redundant) role in early nephrogenesis. Improving patient outcomes requires advances in understanding and targeting of the multiple genes and cellular control pathways now identified as active in WT development. Decades of clinical and basic research have helped to gradually optimize clinical care. Curative therapy is achievable in 90% of affected children, even those with disseminated disease, yet survival disparities within and between countries exist and deserve commitment to change. Updated epidemiological studies have also provided novel insights into global incidence variations. Introduction of biology-driven approaches to risk stratification and new drug development has been slower in WT than in other childhood tumours. Current prognostic classification for children with WT is grounded in clinical and pathological findings and in dedicated protocols on molecular alterations. Treatment includes conventional cytotoxic chemotherapy and surgery, and radiation therapy in some cases. Advanced imaging to capture tumour composition, optimizing irradiation techniques to reduce target volumes, and evaluation of newer surgical procedures are key areas for future research
Keywords: Wilms tumour; tumorigenesis; ACE: Genetic Medicine; WAGMC; University of Ghana; Kayo Nakata; Gordan Vujanic; James I. Gelle